PENGARUH SUPPLY CHAIN MANAGEMENT TERHADAP LOYALITAS KONSUMEN PADA KANTIN UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Malkan Yahya Abdillah; Nurhafifah Saragih; Siti Aisyah (Universitas Bunda Mulia, 2022)
This study aims to determine the effect of supply chain management on consumer loyalty in the canteen of the State Islamic University of North Sumatra partially. The method used in this study is a quantitative research method of causal associative research. Data was collected using the method of observation, questionnaires, and documentation studies. The number of respondents used is (N) = 30. Data processing in this study was carried out using validity, reliability, and simple linear regression analysis. Validity test results show that r-Value > r-Table is 0.361, and the test results reliably indicate that the value of Cronbach's Alpha is greater than 0.6, so that all instruments used in each variable can be said to be valid and reliable. The results of the t-test indicate that the t-count value obtained from the supply chain management (X) variable is 4.188 which is greater than the t-table value of 2.042. Based on its significance value, the supply chain management variable (X) is 0.000, which is smaller than 0.05. The results of this hypothesis test indicate that H0 is rejected and Ha is accepted, which means that partially there is a positive and significant effect of supply chain management on consumer loyalty.